A method for preparing ultra-wide-angle low-reflection composite nanostructure optical film

Through laser etching and chemical treatment, the optical film with a gradient refractive index film layer is solved, and the existing optical film has a high reflectivity problem under large angle incident light is achieved, and ultra-wide angle, low reflectivity and high transmittance are achieved. Effect.

CN119080399BActive Publication Date: 2025-02-11SHENZHEN FORBEST OPTOELECTRONIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411594342.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-11
Estimated Expiration
2044-11-09

AI Technical Summary

Technical Problem

The existing optical film has a high reflectivity under large angle incident light, making it difficult to achieve ultra-wide angle, low reflectivity and high transmittance effects.

Method used

Microstructure array is formed by laser etching treatment of the glass substrate surface, combined with melamine liquid and boric acid treatment, filled with boron nitride to shorten the depth and width of the microstructure array, and coated with rare earth terbium-modified silica layer on the surface to form gradient refraction rate film layer.

Benefits of technology

It realizes the ultra-low reflection effect and high transmittance of the optical film under large angle incident light, and has the advantages of ultra-wide angle, low reflectance and high transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of optical films, and specifically discloses a method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film, comprising the following steps: S1, cleaning the surface of a glass substrate, and then performing laser etching to obtain an etched glass; S2, placing the etched glass in a melamine solution, heating it to 780-800°C for treatment for 30-40 minutes, and obtaining nitrogen-doped glass after cooling; then treating the surface with boric acid and ammonia to obtain a semi-finished product; S3, coating a rare earth terbium-modified silica layer on the surface of the semi-finished product to obtain a finished product; the optical film has the advantages of ultra-wide angle, low reflectivity, and high transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optical films, and more specifically, to a method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film. Background Art

[0002] Optical films are widely used in optical systems, solar cells, optoelectronic devices, display screens, window components and other fields.

[0003] In the field of architecture, low-reflection optical films can be used in office buildings, hotels, shopping malls, etc., which ensure indoor lighting effects and visual comfort by increasing transmittance and reducing reflectivity; in the field of electronic products, the screen protection glass of tablets, mobile phones, TVs and other products can improve clarity and visual effects by reducing reflected light, while protecting the screen from scratches; in the field of optical instruments, telescopes ensure imaging quality by increasing transmittance and reducing the impact of reflected light. The optical film on the camera will easily cause part of the picture to be blurred or various bright spots, halos, purple edges, ghost images and other phenomena to appear if sunlight directly shines into the lens; so how to reduce or eliminate the reflected light on optical surfaces such as lenses, prisms, and plane mirrors, thereby increasing the light transmittance of these components and reducing or eliminating the stray light of the system, has gradually attracted people's attention.

[0004] In the prior art, the types of microstructures of anti-reflective surfaces are generally in the form of pyramids, nano-spikes, gratings, etc. Although the above structures can increase the scattering of light, they are highly dependent on the angle of incident light, and the reflectivity of light incident at a large angle is higher.

[0005] Therefore, how to prepare an optical film with ultra-wide angle, low reflectivity and high transmittance is a problem to be solved. Summary of the invention

[0006] In order to prepare an ultra-wide-angle, low-reflectivity, and high-transmittance optical film, the present application provides a method for preparing an ultra-wide-angle, low-reflectivity composite nanostructure optical film.

[0007] The present application provides a method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film, which adopts the following technical solution:

[0008] A method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film comprises the following steps:

[0009] S1, cleaning the surface of the glass substrate, and then performing laser etching to obtain etched glass;

[0010] S2, soaking the etched glass in melamine solution, taking out the etched glass and scraping off the excess melamine solution on the surface, heating to 780-800°C for 30-40 minutes, cooling to obtain nitrogen-doped glass; then treating the surface with boric acid and ammonia to obtain a semi-finished product;

[0011] S3, coating a rare earth terbium modified silicon dioxide layer on the surface of the semi-finished product to obtain a finished product.

[0012] By adopting the above technical scheme, after the surface of the glass substrate is etched, the surface roughness increases and a microstructure array is generated on the surface of the glass substrate. Under laser etching conditions, it is difficult to etch a structure array with a nanometer depth. After the etched glass is immersed in melamine solution, excess liquid on the surface of the etched glass is scraped off, so that the micro-gaps of the etched glass are easy to load the melamine liquid. Combined with the larger specific surface area of ​​the etched gaps on the glass substrate, it is further easy to load the melamine liquid. Combined with high-temperature gasification treatment, nitrogen in the melamine is doped into the etched gaps in the glass substrate to achieve partial filling of the gaps. After that, the etched gaps are treated with boric acid and ammonia to facilitate the filling of hexagonal boron nitride in the etched gaps. At the same time, nitrogen and hexagonal boron nitride are also doped around the etched gaps, which not only fills the etched gaps and shortens the depth of the microstructure array, but also shrinks the etched gaps. The width of the etching gap is reduced, and the width of the etching gap is the distance between adjacent protrusions in the microstructure array; while the etching depth and width are reduced, the surface of the glass substrate still has a high roughness, forming a hexagonally arranged micro-nano array structure similar to a moth-eye structure, which is convenient for reducing the light reflectivity after multi-angle light is incident, thereby ensuring that the optical film has a high transmittance; finally, a rare earth terbium modified silica layer is coated on the surface of the semi-finished product, and the good anti-reflection effect of rare earth terbium is combined with the transmission effect of the silica layer coating, and the hexagonally arranged micro-nano array structure on the semi-finished product can be equivalent to a gradient refractive index film layer with a continuous gradient change in the refractive index along the depth direction, thereby reducing the reflection phenomenon caused by the sharp change of the refractive index, so that the large-angle incident light has an ultra-low reflection effect, thereby obtaining an optical film with ultra-wide angle, low reflectivity and high transmittance.

[0013] Preferably, the cleaning process specifically comprises the following steps: soaping, then washing with water, and then drying.

[0014] By adopting the above technical solution, after the surface of the glass substrate is cleaned, stains and impurities on the surface are removed to ensure the cleanliness of the surface of the glass substrate and the accuracy and precision of the subsequent processing of the glass substrate, thereby ensuring that the ultra-wide-angle incident light has a low reflection effect, making the optical polishing

[0015] Preferably, the average depth of the laser etching is 1-3 μm, and the average width is 0.5-1 μm.

[0016] By adopting the above technical scheme, the etching depth and average width are limited to ensure that the distance between adjacent protrusions during the etching process is relatively close, and the etching depth can reach the nanometer level after loading nitrogen doping, hexagonal boron nitride and other materials, thereby overcoming the disadvantage that the laser etching depth is not easy to operate to the nanometer level. At the same time, it can also ensure that the size of the micro-nano structure is smaller than the wavelength of visible light, so that the light wave cannot recognize the micro-nano structure network, so that the ultra-wide-angle incident light has an ultra-low reflection effect, ensuring the ultra-wide-angle, low reflection and high transmittance effects of the optical film.

[0017] Preferably, the melamine solution is a melamine aqueous solution with a mass fraction of 1-3%.

[0018] By adopting the above technical scheme, the mass fraction of the melamine aqueous solution is limited to ensure that the melamine liquid reaches the laser-etched gaps on the surface of the glass substrate, thereby achieving the nitrogen doping effect; at the same time, the nitrogen doping of melamine can further assist the filling of hexagonal boron nitride, thereby increasing the hexagonal array arrangement structure of the micro-nano structure on the surface of the glass substrate, reducing the reflection phenomenon caused by the sharp change of the refractive index, thereby increasing the wide-angle range of the incident light, and making the optical film have the advantages of ultra-wide angle and low reflection.

[0019] Preferably, the specific steps of the boric acid and ammonia treatment are as follows:

[0020] The nitrogen-doped glass is immersed in boric acid for 5-15 minutes, excess boric acid on the surface of the nitrogen-doped glass is scraped off, and the glass is processed at 950-1200° C. for 2-4 hours under the condition of passing ammonia gas, and then cooled to room temperature.

[0021] By adopting the above technical scheme, after the nitrogen-doped glass is treated with boric acid, the micro-gap structure on the surface is loaded with boric acid, and then under ammonia conditions, with a limited temperature and reaction time, nano-scale boron nitride particles are gradually generated in the gaps. The boron nitride tends to be hexagonal, which can be similar to the hexagonal structure of a moth eye. The refractive index changes continuously and gradually along the depth direction, which can reduce the reflection phenomenon caused by the sharp change of the refractive index, thereby achieving the effect of ultra-wide-angle anti-reflection, so that the optical film has the advantages of ultra-wide angle, low reflection and high transmittance.

[0022] Preferably, the average depth at the etching position on the surface of the semi-finished product is 100-300 nm.

[0023] By adopting the above technical solution, for the micro-nano structure presenting a nanoscale column array, the size of the micro-nano structure is smaller than the wavelength of the incident light, the incident light is not sensitive to the morphology of the micro-nano structure and will gradually bend, and this moth-eye-like nanostructure or sub-wavelength structure is equivalent to an anti-reflection layer with a gradient refractive index. Even in the case of an ultra-wide angle of incidence, there is still a relatively gentle refractive index gradient between the air and the substrate, so that the optical film can achieve the low refractive index requirements within a wide angle and a wide spectral range, thereby making the optical film have the advantages of ultra-wide angle, low reflection and high transmittance.

[0024] Preferably, the specific steps of coating the surface of the semi-finished product with a rare earth terbium-modified silicon dioxide layer are as follows:

[0025] Weigh ethyl orthosilicate, ethanol and polyethylene glycol solution in a mass ratio of 1:15-25:0.5-1, mix and stir evenly to obtain a dissolving solution; add hydrochloric acid to the ethanol aqueous solution to adjust the pH to 2-2.5 to obtain a mixed solution; add the mixed solution to the dissolving solution in a mass ratio of 1:2.5-3.5, stir at 75-80°C, then add rare earth terbium solution and continue to stir, the rare earth terbium solution accounts for 1%-1.5% of the dissolving solution, seal for 5-8h, and obtain a silicon dioxide sol; the silicon dioxide sol is coated on the surface of the semi-finished product by an immersion pulling method, and then after vacuum drying, the temperature is raised to 200-250°C, stretched, and finally heated to 550-570°C for annealing, and cooled to room temperature.

[0026] By adopting the above technical scheme, the combination of ethyl orthosilicate and polyethylene glycol solution can induce silicon dioxide to form a uniformly distributed film layer, and the dispersion effect of the internal rare earth terbium can form a staggered micro-nano structure. The anti-reflection effect of the rare earth terbium itself can be combined to further improve the anti-reflection effect of the silica gel film layer. Combined with the stretching treatment, the film layer formed by the silica sol is not easy to adhere to the raised position on the surface of the glass substrate, ensuring that the size of the micro-nano structure is smaller than the wavelength of the incident light, so that the optical film has the advantages of ultra-wide angle, low reflectivity and high transmittance.

[0027] Preferably, the rare earth terbium solution is a rare earth terbium hydrochloric acid solution with a concentration of 0.5-1%.

[0028] By adopting the above technical solution, the concentration of rare earth terbium liquid is limited, and the rare earth terbium liquid is evenly dispersed in the silica sol. The anti-reflection effect of rare earth terbium and its own filling effect are combined to further improve the distribution uniformity of the staggered micro-nano structure, thereby further reducing reflection and making the optical film have ultra-wide-angle and low-reflection effects.

[0029] Preferably, the stretching ratio of the stretching treatment is 1.1-1.25 times.

[0030] By adopting the above technical solution and limiting the stretching ratio, the raised vertices of the micro-nano structure on the glass substrate are not easily loaded with the film layer formed by the silica sol, so that the film layer is further dispersed in the gaps of the micro-nano structure, and the depth of the micro-nano structure is controlled to ensure that large-angle incident light still has a low reflection effect when reaching the surface of the optical film.

[0031] Preferably, the heating rate to 200-250°C is 2-5°C / min, and the heating rate to 550-580°C is 8-12°C / min.

[0032] By adopting the above technical solution, the temperature is first increased at a low heating rate and then continued to be increased at a high heating rate, thereby ensuring that the internal crystals of the film layer formed by the silica sol are evenly dispersed and present an interlaced structure, further making the optical film have a lower reflection effect in a large incident angle range, thereby ensuring the transmittance of the optical film.

[0033] In summary, this application has the following beneficial effects:

[0034] 1. A hexagonal structure similar to a moth eye is formed on the surface of the optical film. By limiting the scale of the micro-nano structure, the size of the micro-nano structure is made smaller than the wavelength of visible light, so that the light wave cannot recognize the micro-nano structure; its structural layer can be equivalent to a gradient refractive index film layer with a continuous gradient change in the refractive index along the depth direction, thereby reducing the reflection phenomenon caused by the sharp change of the refractive index, so that the optical film has an extremely low reflection coefficient for visible light in a large incident angle range, so that the optical film has the advantages of ultra-wide angle, low reflectivity and high transmittance at the same time.

[0035] 2. After the etched glass is mixed with melamine liquid, the micro-gaps of the etched glass are easy to load with melamine liquid. After high-temperature gasification treatment, the nitrogen in the melamine is doped into the etched gaps in the glass matrix to achieve partial filling of the gaps. After treatment with boric acid and ammonia, the hexagonal boron nitride is doped to fill the etched gaps, so that the etching depth and width are reduced while the surface of the glass matrix still has a high roughness, so that after multi-angle light is incident, the optical film still has a low reflectivity.

[0036] 3. The rare earth terbium liquid is evenly dispersed in the silica sol, and the anti-reflection effect of the rare earth terbium and its own filling effect further improve the distribution uniformity of the staggered micro-nano structure, thereby further reducing reflection and making the optical film have ultra-wide angle and low reflectivity effects. DETAILED DESCRIPTION

[0037] The present application is further described in detail below with reference to the embodiments.

[0038] The following raw materials are all commercially available. Example

[0039] Example 1: A method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film:

[0040] S1, washing the surface of the glass substrate once with soap, twice with water, and drying to complete the cleaning process, the average thickness of the glass substrate is 0.5 mm, and then performing laser etching on one side of the glass substrate, the average etching depth is 2 μm, the average etching width is 0.8 μm, and an etched glass is obtained;

[0041] S2. Place the etched glass flat in melamine solution and soak it completely for 10 minutes, with the etched surface of the etched glass facing upwards, and the liquid level of the melamine solution being 5 cm higher than the surface of the etched glass. Then, take out the etched glass horizontally, and use a flat plate to scrape off excess melamine solution on the etched side of the etched glass surface. The melamine solution is a 2% by mass melamine aqueous solution, and the temperature is increased to 800°C at a heating rate of 5°C / min for 30 minutes, and then the nitrogen-doped glass is obtained after cooling. Place the nitrogen-doped glass with the etched surface facing upwards in boric acid and soak it horizontally for 10 minutes. Then, take out the nitrogen-doped glass horizontally, and use a flat plate to scrape off excess boric acid on the etched side of the etched glass surface. Under the condition of passing ammonia gas, the glass is processed at 1100°C for 3 hours at a heating rate of 5°C / min, and then cooled to room temperature to obtain a semi-finished product. The average depth of the etching position on the surface of the semi-finished product is 200nm.

[0042] S3, weigh 2kg of tetraethyl orthosilicate, 40kg of ethanol and 1kg of polyethylene glycol solution, mix and stir evenly, the mass fraction of ethanol is 99%, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 2%, and the polyethylene glycol is polyethylene glycol 2000, to obtain a dissolving solution; add hydrochloric acid to the 5% mass fraction ethanol aqueous solution, adjust the pH to 2, and obtain a mixed solution; add 10kg of the mixed solution to 30kg of the dissolving solution, stir at 80°C for 1h, and then add 0.3kg of rare earth terbium solution The stirring treatment was continued, the rare earth terbium solution was a rare earth terbium hydrochloric acid solution with a concentration of 1%, the hydrochloric acid concentration was 5%, and the mixture was sealed for 7 hours to obtain a silica sol; the silica sol was coated on the surface of the semi-finished product by an immersion pulling method, and the silica sol formed a film layer with an average thickness of 50 nm, and then vacuum dried, heated to 200°C at a heating rate of 4°C / min, stretched to a stretching rate of 1.2 times, and finally heated to 560°C at a heating rate of 10°C / min for annealing for 4 hours, cooled to room temperature, and a finished product was obtained.

[0043] Embodiment 2: This embodiment differs from Embodiment 1 in that:

[0044] S1, washing the surface of the glass substrate once with soap, twice with water, and drying to complete the cleaning process, and then performing laser etching on one side of the surface of the glass substrate, with an average etching depth of 3 μm and an average etching width of 1 μm to obtain an etched glass;

[0045] S2, completely immersing the etched glass in melamine solution, then scraping off the excess melamine solution on the etched side of the etched glass surface with a flat plate, heating to 780°C at a heating rate of 5°C / min for 40 minutes, and cooling to obtain nitrogen-doped glass; immersing the nitrogen-doped glass in boric acid for 5 minutes, then scraping off the excess boric acid on the etched side of the etched glass surface with a flat plate, processing at 950°C for 4 hours at a heating rate of 5°C / min under the condition of passing ammonia gas, and then cooling to room temperature to obtain a semi-finished product; the average depth of the etching position on the surface of the semi-finished product is 300nm;

[0046] S3. Weigh 2kg of tetraethyl orthosilicate, 30kg of ethanol and 1kg of polyethylene glycol solution, mix and stir evenly to obtain a dissolving solution; add hydrochloric acid to a 5% by mass ethanol aqueous solution to adjust the pH to 2.5 to obtain a mixed solution; add 10kg of the mixed solution to 25kg of the dissolving solution, stir at 75°C for 1h, then add 0.25kg of rare earth terbium solution and continue stirring, the rare earth terbium solution is a rare earth terbium hydrochloric acid solution with a concentration of 0.5%, seal for 5h, and obtain a silica sol; the silica sol is coated on the surface of the semi-finished product by an immersion pulling method, and then after vacuum drying, it is heated to 200°C at a heating rate of 2°C / min, stretched to a stretching ratio of 1.1 times, and finally heated to 550°C at a heating rate of 8°C / min for annealing for 4h, cooled to room temperature, and obtained a finished product.

[0047] Embodiment 3: This embodiment differs from Embodiment 1 in that:

[0048] S1, washing the surface of the glass substrate once with soap, twice with water, and drying to complete the cleaning process, and then performing laser etching on one side of the surface of the glass substrate, with an average etching depth of 1 μm and an average etching width of 0.5 μm to obtain an etched glass;

[0049] S2, completely immersing the etched glass in melamine solution, then scraping off the excess melamine solution on the etched side of the etched glass surface with a flat plate, heating to 800°C at a heating rate of 5°C / min for 30 minutes, and cooling to obtain nitrogen-doped glass; immersing the nitrogen-doped glass in boric acid for 15 minutes, then scraping off the excess boric acid on the etched side of the etched glass surface with a flat plate, processing at 1200°C for 2 hours at a heating rate of 5°C / min under the condition of passing ammonia gas, and then cooling to room temperature to obtain a semi-finished product; the average depth of the etching position on the surface of the semi-finished product is 100nm;

[0050] S3. Weigh 2kg of tetraethyl orthosilicate, 50kg of ethanol and 2kg of polyethylene glycol solution, mix and stir evenly to obtain a dissolving solution; add hydrochloric acid to a 5% by mass ethanol aqueous solution, adjust the pH to 2, and obtain a mixed solution; add 10kg of the mixed solution to 35kg of the dissolving solution, stir at 80°C for 1h, then add 0.525kg of rare earth terbium solution and continue stirring, the rare earth terbium solution is a 1% rare earth terbium hydrochloric acid solution, seal for 8h, and obtain a silica sol; the silica sol is coated on the surface of the semi-finished product by an immersion pulling method, and then after vacuum drying, it is heated to 250°C at a heating rate of 5°C / min, stretched to a stretching ratio of 1.25 times, and finally heated to 580°C at a heating rate of 12°C / min for annealing for 4h, cooled to room temperature, and obtained a finished product.

[0051] Embodiment 4: This embodiment differs from Embodiment 1 in that:

[0052] The laser etching depth is 5 μm, the average width is 3 μm, and the average depth at the etching position on the surface of the semi-finished product is 600 nm.

[0053] Embodiment 5: This embodiment differs from Embodiment 1 in that:

[0054] During the preparation of the rare earth terbium modified silica layer coated on the surface of the semi-finished product, no polyethylene glycol solution was added.

[0055] Embodiment 6: This embodiment differs from Embodiment 1 in that:

[0056] During the preparation of the rare earth terbium modified silicon dioxide layer coated on the surface of the semi-finished product, no rare earth terbium liquid was added.

[0057] Embodiment 7: This embodiment differs from Embodiment 1 in that:

[0058] During the preparation process of the rare earth terbium modified silica layer coated on the surface of the semi-finished product, no stretching treatment was performed.

[0059] Embodiment 8: This embodiment differs from Embodiment 1 in that:

[0060] During the preparation process of the rare earth terbium modified silica layer coated on the surface of the semi-finished product, the temperature was raised to 200°C at a heating rate of 10°C / min, and the stretching treatment had a stretching ratio of 1.2 times. Finally, the temperature was raised to 570°C at a heating rate of 10°C / min and annealed for 4 hours, and then cooled to room temperature to obtain the finished product. Comparative Example

[0061] Comparative Example 1: The difference between this comparative example and Example 1 is that:

[0062] S2. The etched glass is completely immersed in melamine solution, and then the excess melamine solution on the etched side of the etched glass surface is scraped off with a flat plate. The melamine solution is a 2% by mass melamine aqueous solution, and the temperature is increased to 800°C at a heating rate of 5°C / min for 30 minutes. After cooling, nitrogen-doped glass is obtained; and then the glass is cooled to room temperature to obtain a semi-finished product.

[0063] Comparative Example 2: The difference between this comparative example and Example 1 is that:

[0064] S2. Soak the etched glass in boric acid for 5 minutes, then use a flat plate to scrape off excess boric acid on the etched side of the etched glass surface, process at 1100°C for 3 hours at a heating rate of 5°C / min while passing ammonia gas, then cool to room temperature to obtain a semi-finished product.

[0065] Comparative Example 3: The difference between this comparative example and Example 1 is that:

[0066] S2. The etched glass is completely immersed in melamine solution, and then the excess melamine liquid on the etched side of the etched glass surface is scraped off with a flat plate. The melamine solution is a 2% by mass melamine aqueous solution, and the temperature is increased to 800°C at a heating rate of 5°C / min for 30 minutes, and nitrogen-doped glass is obtained after cooling; the nitrogen-doped glass is immersed in boric acid for 5 minutes, and then the excess boric acid on the etched side of the etched glass surface is scraped off with a flat plate, and the etched glass is processed at 1100°C for 3 hours at a heating rate of 5°C / min under the condition of passing ammonia gas, and then cooled to room temperature to obtain a finished product.

[0067] Performance testing

[0068] 1. Reflectivity detection

[0069] Optical films were prepared by the methods of Examples 1-8 and Comparative Examples 1-3, and the reflectivity was measured at an oblique incident angle of 30° and 80° at a wavelength of 540 nm using a reflectivity detector. Five average values ​​were taken and the data were recorded.

[0070] 2. Transmittance detection

[0071] Optical films were prepared by the methods of Examples 1-8 and Comparative Examples 1-3, and transmittance was measured at an oblique incident angle of 30° and 80° at a wavelength of 540 nm using a transmittance detector. Five average values ​​were taken and the data were recorded.

[0072] Table 1 Performance test table

[0073]

[0074] It can be seen from Examples 1-3 and Table 1 that the optical film prepared in the present application has a low reflectivity, and under conditions of large-angle oblique incident light, the reflectivity is still low, and the transmittance is high, and under conditions of large-angle oblique incident light, the transmittance is still high, indicating that the finished optical film has the advantages of ultra-wide angle, low reflectivity and high transmittance.

[0075] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that the laser etching depth of Example 4 is 5μm, the average width is 3μm, and the average depth at the etching position on the surface of the semi-finished product is 600nm. Compared with Example 1, the reflectivity of the optical film prepared in Example 4 is greater than that of Example 1, and the transmittance is lower than that of Example 1; This indicates that a larger etching depth and width can easily make the size of the micro-nano structure larger than the wavelength of visible light, making it easy for light waves to recognize the micro-nano structure network, thereby making the ultra-wide-angle incident light have a high reflection effect, affecting the ultra-wide-angle, low reflection and high transmittance effects of the optical film.

[0076] In the preparation process of the rare earth terbium-modified silica layer coated on the surface of the semi-finished product of Example 5, no polyethylene glycol solution was added. Compared with Example 1, the reflectivity of the optical film prepared in Example 5 was greater than that of Example 1, and the transmittance was lower than that of Example 1. This shows that the addition of polyethylene glycol solution can not only promote the uniform distribution of crystal types inside the film layer, but also facilitate the formation of more distributed micro-nano structures in combination with rare earth terbium, thereby ensuring that the optical film has the advantages of low reflectivity and high transmittance.

[0077] In the preparation process of the rare earth terbium-modified silica layer coated on the surface of the semi-finished product in Example 6, no rare earth terbium liquid was added. Compared with Example 1, the reflectivity of the optical film prepared in Example 6 was greater than that in Example 1, and the transmittance was lower than that in Example 1; this indicates that rare earth terbium itself has a good anti-reflection effect, and the filling and dispersion effect of rare earth terbium further improves the distribution uniformity of the staggered micro-nano structures in the film layer, thereby further reducing reflection, and at the same time makes the optical film have ultra-wide-angle and low-reflection effects.

[0078] In the process of preparing the rare earth terbium modified silica layer coated on the surface of the semi-finished product of Example 7, no stretching treatment was performed. Compared with Example 1, the reflectivity of the optical film prepared in Example 7 was greater than that in Example 1, and the transmittance was lower than that in Example 1; this indicates that the stretching treatment makes it difficult for the raised vertices of the micro-nano structure on the glass substrate to load the film layer formed by the silica sol, so that the film layer is further dispersed in the gaps of the micro-nano structure, thereby controlling the depth of the micro-nano structure and ensuring that large-angle incident light still has a low reflection effect when reaching the surface of the optical film.

[0079] The heating rate of Example 8 is different. Compared with Example 1, the reflectivity of the optical film prepared in Example 8 is greater than that of Example 1, and the transmittance is lower than that of Example 1; this indicates that the temperature is first increased at a low heating rate and then continued to be increased at a high heating rate, thereby ensuring that the internal crystal forms of the film layer formed by the silica sol are evenly dispersed and present an interlaced structure, and further enabling the optical film to have a lower reflectivity and a higher transmittance within a large range of incident angles.

[0080] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that the etched glass in Comparative Example 1 has not been treated with boric acid and ammonia, and the etched glass in Comparative Example 2 has not been treated with melamine liquid. Compared with Example 1, the reflectivity of the optical films prepared in Comparative Examples 1 and 2 is greater than that in Example 1, and the transmittance is lower than that in Example 1; this indicates that after the etched glass is mixed with the melamine liquid, the micro-gaps of the etched glass are convenient for loading the melamine liquid, and the high-temperature gasification treatment is combined to achieve nitrogen doping into the etched gaps in the glass matrix; and then after the boric acid treatment, it is convenient to fill the etched gaps with hexagonal boron nitride, and the micro-nano structure of the etched gaps can reduce the reflection phenomenon caused by the sharp change of the refractive index, so that after the large-angle light is incident, the optical film has the advantages of low reflectivity and high transmittance.

[0081] In comparative example 3, the uncoated rare earth terbium modified silica layer on the glass surface is etched. Compared with Example 1, the reflectivity of the optical film prepared in comparative example 3 is greater than that in Example 1, and the transmittance is lower than that in Example 1. This indicates that the better anti-reflection effect of rare earth terbium is combined with the transmittance effect of the silica layer coating, and the micro-nano staggered structure on the surface of the finished optical film, to form a hexagonally arranged micro-nano array structure similar to a moth-eye structure, and its structural layer can be equivalent to a gradient refractive index film layer with a continuous gradient change in the refractive index along the depth direction, which can reduce the reflection phenomenon caused by the sharp change of the refractive index, so that the incident light at a large angle has an ultra-low reflection effect, thereby obtaining an optical film with ultra-wide angle, low reflectivity and high transmittance.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film, characterized in that: The steps include: S1, cleaning the surface of the glass substrate, and then performing laser etching to obtain etched glass; S2, soaking the etched glass in melamine solution, taking out the etched glass, scraping off the excess melamine solution on the surface, heating to 780-800°C for 30-40 minutes, and cooling to obtain nitrogen-doped glass; soaking the nitrogen-doped glass in boric acid for 5-15 minutes, scraping off the excess boric acid on the surface of the nitrogen-doped glass, processing at 950-1200°C for 2-4 hours under the condition of passing ammonia gas, and then cooling to room temperature to obtain a semi-finished product; the average depth of the etching position on the surface of the semi-finished product is 100-300nm; S3. Weigh tetraethyl orthosilicate, ethanol and polyethylene glycol solution in a mass ratio of 1:15-25:0.5-1, mix and stir evenly to obtain a dissolving solution; add hydrochloric acid to the ethanol aqueous solution to adjust the pH to 2-2.5 to obtain a mixed solution; add the mixed solution to the dissolving solution in a mass ratio of 1:2.5-3.5, stir at 75-80°C, then add rare earth terbium solution and continue stirring, the rare earth terbium solution accounts for 1%-1.5% of the mass of the dissolving solution, seal for 5-8h, and obtain silica sol; the silica sol is coated on the surface of the semi-finished product by the immersion pulling method, and then after vacuum drying, the temperature is raised to 200-250°C, stretched, and finally heated to 550-580°C for annealing, cooled to room temperature, and obtained a finished product.

2. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The cleaning process specifically includes the following steps: soaping, washing with water, and then drying.

3. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The average depth of the laser etching is 1-3 μm, and the average width is 0.5-1 μm.

4. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The melamine solution is a melamine aqueous solution with a mass fraction of 1-3%.

5. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The rare earth terbium solution is a rare earth terbium hydrochloric acid solution with a concentration of 0.5-1%.

6. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The stretching ratio of the stretching treatment is 1.1-1.25 times.

7. The method for preparing an ultra-wide-angle low-reflection composite nanostructure optical film according to claim 1, characterized in that: The heating rate to 200-250°C is 2-5°C / min, and the heating rate to 550-580°C is 8-12°C / min.

Citation Information

Patent Citations

  • Method for selectively doping emitting stage on surface of crystalline silicon cell film

    CN101866984A

  • Broadband wide-angle anti-reflection composite micro-nano structure surface and preparation method thereof

    CN113740940A